Sales promotion of Slovak food on the Slovakmarket - Jarossová, Malgorzata A. (Engineering Sciences And Technologies, 2017)
The share of foreign food on the Slovak market has increased by about 20% in the last five years. In most cases, food comes from Poland, the Czech Republic, Hungary, Austria, other EU countries, and beyond. This is most visible in retail chains. The share of Slovak food products on the Slovak food market is 37.7% in 2018. The most Slovak products on the domestic market are in the category of milk, water/mineral water, wine, beer, and spirits. The least represented are those in the category of chocolate and non-chocolate confectionery, oil, and canned products. The largest amount of Slovak food is offered to consumers in retail chains such as COOP Jednota (56%) and CBA (50%), the least in Lidl (16%). The aim of the article is to describe various forms of sales promotion of Slovak food on the domestic market. The methods of analysis and synthesis were applied. We described examples of the sales promotion activities carried out by Ministry of Agriculture and Rural Development of the Slovak Republic, civic association, local action groups, Centre for Environmental Activities, and retail chains. “Quality mark SK” is the best known label of Slovak food recognized by Slovak consumers. The information activities regarding it have been conducted for 14 years using different forms of communication, especially TV, billboards, newspaper articles. Shopping patriotism in Slovakia is rising, and between the years 2016 and 2017 the number of people buying Slovak products grew by 4%. However, not all the programs, projects and trademarks informing Slovak consumers about the specific properties of Slovak food are familiar to them. This situation may be caused by the lack of financial resources needed for the implementation of these activities by the entities and limited access to consumers. Sales promotion of Slovak food should be continued in Slovakia in the long term, so consumers are aware that buying Slovak food products with specials labels support domestic food producers and support the domestic economy
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2017, Nr 4 (27), s. 23-40
Keywords: sales promotions; Slovak food; Quality mark SK; retail chains; regional brands; promocja sprzedaży; słowacka żywność; znak jakości SK; sieci handlowe; marki regionalne